2021
DOI: 10.1038/s41598-021-91749-4
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-related bloodstream infection associated with multiple insertions of the peripherally inserted central catheter in patients with hematological disorders

Abstract: Patients with hematological disorders are treated with multiple cycles of chemotherapy. As a result, they often require multiple insertions of the peripherally inserted central catheter (PICC) for prolonged periods of time. Although PICCs have been widely used worldwide in various patients, the safety and feasibility of the multiple insertions of the PICC in this population have not been fully verified. We performed a retrospective analysis to clarify the relationship between complications and multiple PICC in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Thus, it is not surprising that patients with haematological malignancies undergoing therapy are inherently at an increased risk of infection. Among haematological malignancies, acute leukaemia had been shown to be associated with higher infection rates ( 19 ). Notably, approximately half of our patients were diagnosed with underlying acute leukaemia and were undergoing treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is not surprising that patients with haematological malignancies undergoing therapy are inherently at an increased risk of infection. Among haematological malignancies, acute leukaemia had been shown to be associated with higher infection rates ( 19 ). Notably, approximately half of our patients were diagnosed with underlying acute leukaemia and were undergoing treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence rates of PICCR-BSI reported in the literature range widely, from 1.0 to 2.1 per 1000 catheter days in noncancer patients [ 23 , 24 ] and from 2.0 to 4.0 per 1000 catheter days in patients with hematological malignancies [ 20 , 21 , 22 ] or solid tumors [ 8 ]. We found that the incidence rate of PICCR-BSI was twice as high in cancer patients treated with chemotherapy as in noncancer patients, which is consistent with previous reports [ 8 , 20 , 21 , 22 , 23 , 24 ]. Among cancer patients, those with hematological malignancies, especially those with leukemia or high-grade lymphoma, are at higher risk for PICCRI compared with patients with solid tumors [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cancer patient remains fragile and susceptible to infections; therefore, maximum precautions should be taken to limit PICCRI. It seems also important to limit the catheter dwell time [ 9 ], particularly in patients with hematological malignancies [ 20 ]. Although this risk factor remains debated [ 22 ], many studies [ 1 , 20 , 29 ] encouraged clinicians to limit the PICC indwelling time to approximately 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CRDTV rate observed is not higher than other catheter types. 23 The higher risk recognized in current literature 1 depends on various factors. The new materials, insertion techniques, and the attention to the position of the tip may have contributed to the observed risk reduction.…”
Section: Discussionmentioning
confidence: 99%